Respiratory syncytial virus immunization in children: The old, the new and what’s just around the corner - Bosco A. Paes; Fabiana Bacchini; Marianne Bracht; Barry Rodgers-Gray; Xavier Carbonell-Estrany (Human Vaccines & Immunotherapeutics, 2025)
Respiratory syncytial virus (RSV) remains a leading cause of severe lower respiratory tract infection, hospitalization, morbidity and mortality in young children. This review summarizes current RSV immunization strategies and parental perspectives on their use. Until recently, immunization was limited to high-risk infants and children, including those born prematurely or with significant co-morbidities, via monthly dosing with the monoclonal antibody (mAb) palivizumab. Recent approvals of long-acting mAb nirsevimab and the maternal RSV pre-fusion F vaccine combined with other anticipated options such as long-acting mAb clesrovimab, and future pediatric vaccines, signal a shift in RSV immunization. Research studies revealed that consistent education and information on RSV for both, healthcare providers and parents is essential for the immunization program success. We report findings from a survey assessing the level of immunization acceptance among Canadian parents. Provision of education through healthcare professionals, printed materials, parent groups, social media, and the internet were recommended.